Molecular, viral and clinical features of alcohol- and non-alcohol-induced liver injury - Neuman, Manuela G.; Seitz, Helmut K.; Teschke, Rolf; Malnick, Stephen; Johnson-Davis, Kamisha L.; Cohen, Lawrence B.; German, Anit; Hohmann, Nicolas; Moreira, Bernhardo; Moussa, George; Opris, Mihai (Current issues in molecular biology, 2022)
Hepatic cells are sensitive to internal and external signals. Ethanol is one of the oldest and most widely used drugs in the world. The focus on the mechanistic engine of the alcohol-induced injury has been in the liver, which is responsible for the pathways of alcohol metabolism. Ethanol undergoes a phase I type of reaction, mainly catalyzed by the cytoplasmic enzyme, alcohol dehydrogenase (ADH), and by the microsomal ethanol-oxidizing system (MEOS). Reactive oxygen species (ROS) generated by cytochrome (CYP) 2E1 activity and MEOS contribute to ethanol-induced toxicity. We aimed to: (1) Describe the cellular, pathophysiological and clinical effects of alcohol misuse on the liver; (2) Select the biomarkers and analytical methods utilized by the clinical laboratory to assess alcohol exposure; (3) Provide therapeutic ideas to prevent/reduce alcohol-induced liver injury; (4) Provide up-to-date knowledge regarding the Corona virus and its affect on the liver; (5) Link rare diseases with alcohol consumption. The current review contributes to risk identification of patients with alcoholic, as well as non-alcoholic, liver disease and metabolic syndrome. Additional prevalence of ethnic, genetic, and viral vulnerabilities are presented.